Unraveling the gut health puzzle: exploring the mechanisms of butyrate and the potential of High-Amylose Maize Starch Butyrate (HAMSB) in alleviating colorectal disturbances - Cheng, Junrui; Zhou, Jing (Frontiers in Nutrition, 2024)
Colorectal disturbances encompass a variety of disorders that impact the colon and rectum, such as colitis and colon cancer. Butyrate, a short-chain fatty acid, plays a pivotal role in supporting gut health by nourishing colonocytes, promoting barrier function, modulating inflammation, and fostering a balanced microbiome. Increasing colorectal butyrate concentration may serve as a critical strategy to improve colon function and reduce the risk of colorectal disturbances. Butyrylated high-amylose maize starch (HAMSB) is an edible ingredient that efficiently delivers butyrate to the colon. HAMSB is developed by esterifying a high-amylose starch backbone with butyric anhydride. With a degree of substitution of 0.25, each hydroxy group of HAMSB is substituted by a butyryl group in every four Dglucopyranosyl units. In humans, the digestibility of HAMSB is 68% (w/w), and 60% butyrate molecules attached to the starch backbone is absorbed by the colon. One clinical trial yielded two publications, which showed that HAMSB significantly reduced rectal O 6 -methyl-guanine adducts and epithelial proliferation induced by the high protein diet. Fecal microbial profiles were assessed in three clinical trials, showing that HAMSB supplementation was consistently linked to increased abundance of Parabacteroides distasonis. In animal studies, HAMSB was effective in reducing the risk of diet-or AOMinduced colon cancer by reducing genetic damage, but the mechanisms differed. HAMSB functioned through affecting cecal ammonia levels by modulating colon pH in diet-induced cancer, while it ameliorated chemical-induced colon cancer through downregulating miR19b and miR92a expressions and subsequently activating the caspase-dependent apoptosis. Furthermore, animal studies showed that HAMSB improved colitis via regulating the gut immune modulation by inhibiting histone deacetylase and activating G protein-coupled receptors, but its role in bacteria-induced colon colitis requires further investigation. In conclusion, HAMSB is a food ingredient that may deliver butyrate to the colon to support colon health. Further clinical trials are warranted to validate earlier findings and determine the minimum effective dose of HAMSB.